etermination of Some Phenols in Tigris River by HPLC - Shamar, Jasim M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study describes the determination of some phenols in four different zones of Tigris river in Iraq including, AL-Krieat, AL-Kadhimiya, AL-Jadiriyah, and AL-Adhamiyah. The phenolic compounds analyzed were (2,3-dimethylphenol, 4-chlorophenol, 3-nitrophenol and 2,4-dinitrophenol) using reverse phase high performance liquid chromatography (RPHPLC) with a UV detector on ODS-C18 column(150×4.6 mm I.D) and a mobile phase consisted of methanol-water(30:70)%(v/v) at pH 5.0, and a column temperature at 30C° with 20 µL injection. UV detection helps to identify different phenols at wave length at 280 nm with a flow rate at 0.5 ml/min. The separation time was (< 6) min.The results indicated that the AL-Adhamiyah zone contains the highest concentration of 3-nitrophenol (0.094 µg/mL), while the AL-Jadiriyah zone recorded the lowest concentration of 3-nitrophenol (0.056 µg/mL).On the other hand the other phenolic compounds studied did not record any concentration in four zones of Tigris river. The values of correlation coefficient and accuracy were calculated for 3-nitrophenol, the graph was linear with very good correlation coefficient (R2>0.9999).